2014
DOI: 10.1055/s-0034-1379255
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Electrophilic Amination Reactions To Form Nitrogen-Bearing Tetrasubstituted Carbon Stereocenters

Abstract: The catalytic asymmetric electrophilic amination has been established as a fruitful methodology for the construction of nitrogen-bearing tetrasubstituted carbon stereocenters, with its roots nourished by the latest achievements in chiral catalysis and synthetic strategies. This review summarizes the recent progresses, briefly discusses the reaction mechanism and challenges in this context, and outlines synthetic opportunities for future development. 3 Amination Reactions Using other Amination Reagents 4 Conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(30 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…In comparison, the electrophilic amination of carbon-based nucleophiles has received much less attention. 4 6 This latter strategy is particularly relevant for the enantioselective synthesis of α-tertiary amines, since the catalytic asymmetric addition of nucleophiles to ketimines is an extremely challenging process. 5 Indeed, the direct catalytic enantioselective α-amination of carbonyl compounds 6 has proven to be a useful strategy to access molecules decorated with tetrasubstituted N-containing stereogenic centers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, the electrophilic amination of carbon-based nucleophiles has received much less attention. 4 6 This latter strategy is particularly relevant for the enantioselective synthesis of α-tertiary amines, since the catalytic asymmetric addition of nucleophiles to ketimines is an extremely challenging process. 5 Indeed, the direct catalytic enantioselective α-amination of carbonyl compounds 6 has proven to be a useful strategy to access molecules decorated with tetrasubstituted N-containing stereogenic centers.…”
Section: Introductionmentioning
confidence: 99%
“… 4 6 This latter strategy is particularly relevant for the enantioselective synthesis of α-tertiary amines, since the catalytic asymmetric addition of nucleophiles to ketimines is an extremely challenging process. 5 Indeed, the direct catalytic enantioselective α-amination of carbonyl compounds 6 has proven to be a useful strategy to access molecules decorated with tetrasubstituted N-containing stereogenic centers. However, these reactions rely on the use of aldehydes 7 or activated carbonyl compounds such as 1,3-dicarbonyls, 8 α-cyanocarbonyls, 9 α-keto esters, 10 and 2-oxindoles.…”
Section: Introductionmentioning
confidence: 99%
“…sp 3 ‐rich cycles or quaternary carbons) can correlate to an increase in the selectivity, potency and metabolic stability of drug candidates, along with the successful progression from clinical stages to drug approval . However, due to their congested nature, the incorporation of N‐containing quaternary stereocenters into small molecules poses a synthetic challenge for organic chemists . As a result, small molecules bearing this particular feature are still under‐represented in probe and drug discovery screening collections.…”
Section: Introductionmentioning
confidence: 99%
“…From a synthetic perspective, despite all the advances made in the field of asymmetric catalysis to generate α‐branched amino‐containing compounds, the majority of the reported reactions are based on simple scaffolds with restricted structural diversity and there has been a limited exploration into the construction of such motifs into more complex molecules. It has, however, been demonstrated that the use of α,α‐disubstituted amino esters as subunits to prepare complex molecules bearing this sterically hindered motif can be particularly effective.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, significant advances have been achieved in the metal-catalyzed or organocatalytic asymmetric electrophilic -amination of carbonyl compounds with during the past years [15][16][17][18][19]. In fact, chiral carbonyl derivatives bearing stereogenic -amine substitution are widely distributed among pharmaceutically active compounds.…”
Section: Introductionmentioning
confidence: 99%